2020
DOI: 10.1136/bmjopen-2020-041281
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive patterns, pregnancy outcomes and parental leave practices of women physicians in Ontario, Canada: the Dr Mom Cohort Study protocol

Abstract: IntroductionSurveys and qualitative studies suggest that women physicians may delay childbearing, be at increased risk of adverse peripartum complications when they do become pregnant, and face discrimination and lower earnings as a result of parenthood. Observational studies enrolling large, representative samples of women physicians are needed to accurately evaluate their reproductive patterns, pregnancy outcomes, parental leave practices and earnings. This protocol provides a detailed research plan for such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 46 publications
1
16
0
2
Order By: Relevance
“…The referenced studies by the authors 8,9 were conducted with grant funding from Physicians' Services Incorporated Foundation.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The referenced studies by the authors 8,9 were conducted with grant funding from Physicians' Services Incorporated Foundation.…”
Section: Fundingmentioning
confidence: 99%
“…Women physicians face difficult decisions as to whether they will have children, when, and how many, while still pursuing their career goals. We recently mapped the trajectory of childbirth in women physicians in a populationbased study using data from Ontario, Canada 8,9 and found that the culture of delay starts early and persists throughout postgraduate training. We found a significantly reduced rate of childbirth among women physicians compared with nonphysicians overall, and an accelerated rate of childbirth only at later reproductive ages, suggesting that women physicians appeared to defer pregnancy until after training, with specialists delaying pregnancy longer than family physicians.…”
mentioning
confidence: 99%
“…We therefore examined the odds of maternal and neonatal morbidity in physicians compared with nonphysicians using a unique linkage of physician registration data with population-based administrative data in Ontario, Canada. 19 …”
Section: Introductionmentioning
confidence: 99%
“…le choix d'avoir ou non des enfants, à quel moment, com bien, tout en essayant d'atteindre leurs objectifs profession nels. Nous avons récemment cartographié la trajectoire de l'accouchement chez les femmes médecins dans le cadre d'une étude populationnelle faisant appel à des données onta riennes, au Canada8,9 . Nous avons découvert que cette culture de report se manifeste de façon précoce et persiste tout au long…”
unclassified
“…Soutien financier : Parmi les études citées, celles réalisées par les auteures 8,9 ont obtenu le soutien financier de la fondation Physicians' Services Incorporated.…”
unclassified